Comparing the efficacy of intense pulsed light combined with oral azithromycin versus oral azithromycin alone in the treatment of moderate to severe papulopustular acne vulgaris - Niloofar Afshari; Mehdi Amirnia; Davod Ahmadi; Saeed Kashefi; Vahideh Aghamohammadi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Rising follicular keratin secretion, increasing sebum production, and Propionibacterium acnes are among the main etiology of acne vulgaris formation. Antibiotics are the predominant conventional treatment of acne. Antibiotic resistance is the main problem in the ordinary treatments of acne. Therefore, newer treatments are necessary. Intense pulsed light (IPL) is a novel therapeutic option with rapid application in this field. Methods: Patients referred to us were randomized into two groups: group A (cases) and group B (controls). In addition to conventional antibiotic therapy, IPL was prescribed to group A while azithromycin alone was prescribed to group B. IPL treatment was performed weekly for five weeks and the patients were followed for three months. Declining inflammatory lesions count after the intervention was considered the remission scale. Results: In group A, moderate, partial, and complete remission occurred in 4, 9, and 7 patients, respectively. In group B, moderate, partial, and complete remission occurred in 10, 7, and 3 patients, respectively. Statistically, the remission difference was meaningful between the two groups. Conclusion: IPL with conventional antibiotics is an effective treatment choice in moderate to severe acne vulgaris but also is a more accelerating agent in treatment versus antibiotics alone.